Application of Marine Algae in Water Pollution Control. Issue 1 (January 2022) - Tang, Junyu; Liang, Qizhao; Li, Changling; Huang, Xianghu; Xian, Xiaoqing; Li, Jinhe; Shang, Zhuangzhuang; Pang, Chunjin; Liu, Yu; Zhang, Rui
Abstract: Water pollution is mainly caused by chemical pollution, especially inorganic and organic pollutants, including toxic metals and metalloids as well as various synthetic or organic chemicals. Marine algae have good adsorption capacity for heavy metals such as As, Zn, Cu, Cd, Pb et.al in polluted water, and can also have certain removal ability for pollutants such as nitrogen and phosphorus in sewage. This paper reviews the current application status of wastewater treatment and the mechanism and application of marine algae in wastewater treatment, aiming at providing reference for further research and development of marine algae in wastewater treatment.